Avaliação da deposição da calda de pulverização em função do tipo de ponta e do volume de aplicação, na cultura da soja - Boschini, Laercio (2006)
The soybean has great economical importance in Brazilian agribusiness, and the cultivation with high profitability, it is necessary the use all available technologies in the market and, among them, it is the application technology of agricultural pesticide, that it looks tirelessly for the best technique of the product biologically active it reaches the objective, providing for the effective control of the harmful plant, insect or mushroom, allowing the plant express all the productive potential, when appropriately nurtured and in good environmental conditions. Due to those needs the present work was carried out in Cascavel PR, in the harvest 2004/2005, using the soybean cultivar CD 202, with the objective evaluating the amount spray deposited on the soybean leaves, varied the flow rate applied and the nozzles types used in the spraying boom, used tracer substance, simulating the physical characteristics of the solutions of the products. To evaluate the spraying distribution, fifteen leaves were collected per plant in different extracts (upper, medium and lower), with the purpose of evaluating the syrup penetration, in agreement with the different beaks and applied volumes. The experimental design was arranged in randomized complete blocks, in factorial arrangement, with four beaks and point of the type single fan, double fan, double fan with air induction and rollowcone and 3 syrup volumes (100, 200 and 300 L ha-1). In agreement with the results obtained and in the conditions that the present work was carried out. - The syrup volume that presented larger depositions, in the different levels was 300 L ha-1. - The spraying that presented larger depositions, in the higher levels plants was the double fan nozzles and, for the medium and lower extracts, was the rollowcone nozzle. - The depositions happened in the thirds medium and lower of the soybeans plants were lower significantly to obtained them in the upper third, independently the and the flow rate that was used. - For larger depositions in the upper third of the soybeans plants, the best combination is to use of double plane jet, with of 300 L. - For larger depositions in the medium and lower third of the soybeans plants, the best combination is to use of rollowcone, with flow rate of 200 or 300 L ha-1